The tardigrade fauna of Australian marine caves:With descriptions of nine new species of Arthrotardigrada - Jørgensen, Aslak; Boesgaard, Tom M.; Møbjerg, Nadja; Kristensen, Reinhardt M. (Zootaxa, 2014)
Marine caves are known to support a rich macrofauna; however, few studies have focused on meiofauna. Marine cave meiofaunal tardigrades have been reported from Japan and the Mediterranean Sea and a preliminary list of species including a redescription of Actinarctus neretinus Grimaldi de Zio, D’Addabbo Gallo, Morone De Lucia, Vaccarella and Grimaldi, 1982 was reported from Fish Rock Cave and Jim’s Cave on the coast of Australia. This study is the fourth in a series describing the unique meiofauna in two Australian submarine caves located off the coast of New South Wales, describing nine new species. Only 67 tardigrades were collected from the two caves, yet these contained a high diversity of at least 16 different species which are quite different in the two caves. The fauna includes nine arthrotardigrade genera: Actinarctus, Batillipes, Dipodarctus, Halechiniscus, Raiarctus, Styraconyx, Tanarctus, Tholoarctus, and Wingstrandarctus. This fauna is different from that reported for the high energy beaches along the East Coast of Australia. We describe nine new species comprising a single batillipedid and eight halechiniscids: Batillipes solitarius nov. sp., Dipodarctus australiensis nov. sp., Dipodarctus susannae nov. sp., Raiarctus jesperi nov. sp., Raiarctus katrinae nov. sp., Tanarctus hirsutospinosus nov. sp., Tholoarctus oleseni nov. sp., Wingstrandarctus stinae nov. sp. and Wingstrandarctus unsculptus nov. sp.